2017
DOI: 10.3390/su9122268
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Trends of Carbon Intensities among 127 Countries

Abstract: Many countries in the world have been experiencing widely varying rates of change in their carbon intensity (CI) of economic output. The dynamic trend of CI in this research is measured by the progress ratio (PR) from an experience curve (EC) involving 127 countries during the period of 1980-2011. The overall average PR of 88.8% estimated for the total group of 127 indicates a decreasing trend of carbon intensity. This means that each doubling of the cumulative CO 2 emission by this group has reduced carbon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Using the slacks-based measure (SBM) approach, Wang et al (2017a) found a lower performance in Asia than in Europe and the Americas, yet the Asian countries had the greatest potential in performance improvement. Chang et al (2017) studied dynamic trends of carbon intensity of 127 countries from 1980-2011. Their findings indicated a decreasing trend of carbon intensity in general, yet the decreasing rates for individual countries were divergent to a great extent and most middle-and low-income economies experienced a growing trend of CIs.…”
Section: Cross-country Comparison Of Carbon Emission Performancementioning
confidence: 99%
“…Using the slacks-based measure (SBM) approach, Wang et al (2017a) found a lower performance in Asia than in Europe and the Americas, yet the Asian countries had the greatest potential in performance improvement. Chang et al (2017) studied dynamic trends of carbon intensity of 127 countries from 1980-2011. Their findings indicated a decreasing trend of carbon intensity in general, yet the decreasing rates for individual countries were divergent to a great extent and most middle-and low-income economies experienced a growing trend of CIs.…”
Section: Cross-country Comparison Of Carbon Emission Performancementioning
confidence: 99%
“…Another type of EC-known as kinked EC-can detect whether a statistically-significant shift in a slope may have occurred during the sample period. For example, in a recent study on the dynamic slopes of carbon intensities [47], a majority of 73 out of 127 countries displayed kinked slopes during the 1980-2012 period. In these two EC models, the dependent variable is PME measured in µg/m 3 per person for a given country that can be viewed as the unit penalty or unit cost derived from PM 2.5 concentration experienced per person.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, EC has been used to project CO 2 emissions until 2040 for seven major emitting countries and three regions of the world [46]. Further, EC has been used to estimate the dynamic trends of CIs for 127 countries [47]. As for the application of EC in energy technologies, a review article by Weiss et al [48] presented the PR for 75 energy demand technologies with an average PR of 82%.…”
Section: Experience Curve Applications In Energy and Air Pollutionmentioning
confidence: 99%
“…Thus, numerous mitigation strategies have been proposed to mitigate GHG emissions. A total of 127 countries have already announced their carbon emission reduction timetables [3]. As the largest emitter, China has set its goals for carbon peak and carbon neutralization by 2030 and 2060, respectively.…”
Section: Introductionmentioning
confidence: 99%